Developing a self-help guide for traumatised university students in Iraq - Jaber, Saad Sabet (2012)
Background: Iraqi people have been experiencing traumatic events continually for several decades. Consequently, high prevalence rates of trauma-related symptoms have been documented. In contrast, there is a clear lack in mental health services available for traumatised people. This study aimed to screen for PTSD, depression, and anxiety, assess related variables (e.g. coping strategies, posttraumatic cognitions, and social support), and develop a self-help guide (SHG) for traumatised university students. Methods: Self-report scales were validated via two studies. The first study validated three scales, including Baghdad Trauma History Screen (BTHS), Brief Cope, and Social Support in a sample of 360 (140 males, 220 females) university students. In the second study, the psychometric properties of the scales of Posttraumatic Stress Symptoms (SPTSS), Posttraumatic Cognitions Inventory (PCTI), and the Hospital Anxiety and Depression Scale (HADS) were gained in a sample of 505 (199 males, 306 females) university students. The SHG was developed. Its effectiveness was examined in a sample of participants who reported symptoms that fully met PTSD criteria. The sample included 125 participants: 65 in the experimental group (used the guide for six weeks) and 60 in the control group (did not use the guide). Baseline tests were conducted in both groups before conducting the experiment and post tests afterward. In addition, focus groups were conducted with experts and university students to evaluate the SHG. Results: The scales were reliable and valid. Eighty four percent (424/505) of participants reported at least one traumatic event. Thirty five percent of 424 traumatised students fully met the DSM-IV criteria for PTSD with high levels of Depression and anxiety. Only 11% of participants reported no symptoms at all. Females reported more symptoms than males. The results also revealed that active coping, seeking support, and perceived social support from family was associated with low levels of PTSD, while high levels of PTSD related to the number of traumatic events either experienced by participants themselves or their family members or friends, non problem focused coping, negative posttraumatic cognitions about self and the total posttraumatic negative cognitions. After using the SHG, there were significant increases in the tendency to use active and seeking support coping and significant decreases in non problem-focused coping, negative cognitions about self and the total negative cognitions. There was a significant reduction in levels of PTSD. This reduction related to re-experiencing and avoidance symptoms but not hyperarousal. The level of depression was also reduced. Anxiety was not reduced. However, the experiment was not double blind due to practical reasons and this may influence the results. Conclusion: using the SHG enhanced coping strategies and reduced negative cognitions about self. This led to a reduction in PTSD and depression. Several implications were presented. In addition, self-report scales that validated in this study can be used in future research in the field of traumatic stress in Arabic-speaking populations.